Imagen Institucional de la Gestión Administrativa en el Distrito de Salud 12D01 - Zambrano Vera, Joselin Nicol (2017)
In the health district 12D01, it is evident that the development of activities in the administrative area has a great influence on this institution, which is why it is very important to review how the institutional image of this management is and how it contributes to the development of the goals proposed in function of the fulfillment of the planning presented by the Ministry of Health as executing arm of the policies of the state in relation to the good life, attached to the constitutional norm of service to the citizenship